Location privacy-preserving method in LBS based on Voronoi division - AChun-guang M; HOUChang-li Z; ANGSong-tao Y; HAOYun-long Z (Tongxin xuebao)
In view of low efficiency when the anonymous server faces a large number of users,a cooperative anonymous method is proposed for static and dynamic users respectively.Based on the Voronoi division of the global area,a central server organizes the users in its region to achieve cooperative anonymity,the server needn't construct anonymous region alone for each user,and the burden of the server is reduced.In view of providing actual location when users query from a LBS server,a decrease nearest neighbor query algorithm is proposed.A user's actual location is replaced with a stationary anchor location and gets the points of interest candidate set from the LBS server gradually.By running the algorithm,pre-cise results can be got and avoiding exposure to a user's location privacy.The algorithm can also help to reduce the possi-bility of location inference when the anchor chooses closely to the user.Experiments show that our method can guarantee the user's location privacy,and provide a good working efficiency.